982. Summer Outbreak of Severe RSV-B Disease, Minnesota, 2017. (26th November 2018) - Thielen, Beth; Bye, Erica; Wang, Xiong; Friedlander, Hannah; Maroushek, Stacene; Shilts, Meghan; Strain, Anna; Como-Sabetti, Kathryn; Ferrieri, Patricia; Lynfield, Ruth
Abstract: Background: Respiratory syncytial virus (RSV) causes seasonal outbreaks peaking from October to April in the United States. While symptoms are typically mild and limited to the upper respiratory tract in older children and adults, RSV can cause severe lower respiratory disease, hospitalization and death, particularly among younger children, the immunocompromised and the elderly. During summer 2017, the Minnesota Department of Health (MDH) received a report of a cluster of severe respiratory illness in children with RSV-B infection admitted at an urban county hospital. Methods: MDH conducts surveillance for RSV in Minneapolis-St. Paul with collection of respiratory specimens and clinical and demographic data. We compared characteristics of cases reported in summer 2017 with the previous 4 summer seasons. To understand the genetic relatedness among viruses, we performed complete genome sequencing from primary specimens using an Illumina MiSeq platform employing both a sequence-independent sequencing method and an RSV-specific, overlapping PCR-based approach. Results: From May to September 2017, 58 cases of RSV (48 RSV-B) were reported to MDH compared with 18 (7 RSV-B) during the same period in 2016, 27 in 2015, and 29 in 2014. The median age and frequency of co-morbidities were similar across years; however, 50% required ICU admission in 2017 compared with 12% in preceding 3 years. The RSV-B genome was sequenced from 10 specimens from March to May 2016, 20 specimens from May to September 2017 and 30 specimens from October 2017-January 2018. Phylogenic analysis revealed that 15 cases from May to September. 2017 formed a unique clade distinct from the lineage encompassing 2016 cases from Minnesota and 35 representative complete RSV genomes in GenBank isolated from 6 continents over 13 years. From October 2017 to January 2018, we detected co-circulation of viruses from both lineages among older adults and children. Conclusion: We identified an outbreak of RSV-B associated with severe disease among urban Minnesota children during a time of expected low RSV circulation. Complete genome sequencing data suggested emergence of a new lineage distinct from viruses circulating in Minnesota during the previous season. Genomic characterization can provide useful insights into epidemiologic variations. Disclosures: All authors: No reported disclosures.